The Co-occurrence of Chronic Hepatitis B and Fibrosis Is Associated With a Decrease in Hepatic Global DNA Methylation Levels in Patients With Non-alcoholic Fatty Liver Disease - Li, FangYuan; Ou, Qian; Lai, ZhiWei; Pu, LiuZhen; Chen, XingYi; Wang, LiRong; Sun, LiuQiao; Liang, XiaoPing; Wang, YaoYao; Xu, Hang; Wei, Jun; Wu, Feng; et al. (Frontiers in Genetics, 2021)
Global DNA hypomethylation has been reported in patients with chronic hepatitis B (CHB) and non-alcoholic fatty-liver disease (NAFLD). However, the global DNA methylation profile of patients with concurrent NAFLD and CHB (NAFLD + CHB) is still unclear. We aimed to detect the hepatic global DNA methylation levels of NAFLD + CHB patients and assess the associated risk factors. Liver biopsies were collected from 55 NAFLD patients with or without CHB. The histological characteristics of the biopsy were then assessed. Hepatic global DNA methylation levels were quantified by fluorometric method. The hepatic global DNA methylation levels in NAFLD + CHB group were significantly lower than that in NAFLD group. Participants with fibrosis showed lower levels of hepatic global DNA methylation than those without fibrosis. Participants with both CHB and fibrosis had lower levels of hepatic global DNA methylation than those without either CHB or fibrosis. The co-occurrence of CHB and fibrosis was significantly associated with a reduction in global DNA methylation levels compared to the absence of both CHB and fibrosis. Our study suggests that patients with NAFLD + CHB exhibited lower levels of global DNA methylation than patients who had NAFLD alone. The co-occurrence of CHB and liver fibrosis in NAFLD patients was associated with a decrease in global DNA methylation levels.